Stoichiometry of the Gene Products From the Tetrachloroethene Reductive Dehalogenase Operon pceABCT - Cimmino, Lorenzo; Schmid, Adrien W.; Holliger, Christof; Maillard, Julien (Frontiers in Microbiology, 2022)
Organohalide respiration (OHR) is a bacterial anaerobic process that use halogenated compounds, e.g. tetrachloroethene (PCE), as terminal electron acceptors. Our model organisms are Dehalobacter restrictus strain PER-K23, an obligate OHR bacterium (OHRB), and Desulfitobacterium hafniense strain TCE1, a bacterium with a versatile metabolism. The key enzyme is the PCE reductive dehalogenase (PceA) that is encoded in the highly conserved gene cluster (pceABCT) in both above-mentioned strains, and in other Firmicutes OHRB. To date, the functions of PceA and PceT, a dedicated molecular chaperone for the maturation of PceA, are well defined. However, the role of PceB and PceC are still not elucidated. We present a multilevel study aiming at deciphering the stoichiometry of pceABCT individual gene products. The investigation was assessed at RNA level by reverse transcription and (quantitative) polymerase chain reaction, while at protein level, proteomic analyses based on parallel reaction monitoring were performed to quantify the Pce proteins in cell-free extracts as well as in soluble and membrane fractions of both strains using heavy-labelled reference peptides. At RNA level, our results confirmed the co-transcription of all pce genes, while the quantitative analysis revealed a relative stoichiometry of the gene transcripts of pceA, pceB, pceC and pceT at approximately 1.0:3.0:0.1:0.1 in D. restrictus. This trend was not observed in D. hafniense strain TCE1, where no substantial difference was measured for the four genes. At proteomic level, an apparent 2:1 stoichiometry of PceA and PceB was obtained in the membrane fraction, and a low abundance of PceC in comparison to the other two proteins. In the soluble fraction, a 1:1 stoichiometry of PceA and PceT was identified. In summary, we show that the pce gene cluster is transcribed as an operon with, however, a level of transcription that differs for individual genes, an observation that could be explained by post-transcriptional events. Despite challenges in the quantification of integral membrane proteins such as PceB and PceC, the similar abundance of PceA and PceB invites to consider them as forming a membrane-bound PceA2B protein complex, which, in contrast to the proposed model, seems to be devoid of PceC.